The association between family history of diabetes mellitus and offspring long‐term neurological hospitalisation. (16th November 2019) - Moscovici, Khen; Wainstock, Tamar; Sheiner, Eyal; Pariente, Gali
Abstract: Aim: The aim of the present study was to determine whether being born to non‐diabetic mother with a family history of diabetes mellitus (DM) is associated with higher rates of long‐term neurological hospitalisations of the offspring. Methods: A retrospective analysis of all live births and paediatric hospitalisations at Soroka University Medical Center between 1991 and 2014 was performed. Family history of DM was collected from prepartum women using anamnesis. During the study period, 208 728 deliveries met the inclusion criteria, and of them 8.2% (n = 17 040) were of non‐diabetic mothers with family history of DM. Rates of neurological hospitalisation with or without family history were analysed. Results: Offspring born to non‐diabetic mothers with family history of DM had higher rates of neurological hospitalisations. The cumulative incidence of long‐term neurological hospitalisations was higher as compared with those without family history of DM (log‐rank test P = .007). Neurological hospitalisations was higher by 13% in the study group, after controlling for confounders such as maternal age, maternal obesity, hypertensive disorders, birth weight and caesarean delivery. (adjusted odds ratio 1.13, 95% confidence interval 1.04‐1.23). Conclusion: Being born to a non‐diabetic mother with a family history of DM is independently associated with higher long‐term neurological hospitalisations of the offspring. Abstract :